Antibiotic resistance : mechanisms and new antimicrobial approaches - Kon, Kateryna Volodymyrivna; Rai, Mahendra (Amsterdam : Elsevier, Academic Press, 2016)
"Antibiotic Resistance: Mechanisms and New Antimicrobial Approaches discusses up-to-date knowledge in mechanisms of antibiotic resistance and all recent advances in fighting microbial resistance such as the applications of nanotechnology, plant products, bacteriophages, marine products, algae, insect-derived products, and other alternative methods that can be applied to fight bacterial infections. Understanding fundamental mechanisms of antibiotic resistance is a key step in the discovery of effective methods to cope with resistance. This book also discusses methods used to fight antibiotic-resistant infection based on a deep understanding of the mechanisms involved in the development of the resistance"--
Includes bibliographical references and index.
Keywords: Drug resistance in microorganisms; Drug Resistance, Microbial; Anti-Infective Agents; Nanotechnology; Drug resistance in microorganisms